2016
DOI: 10.1016/j.ygyno.2016.03.020
|View full text |Cite
|
Sign up to set email alerts
|

The High Mobility Group A1 ( HMGA1 ) gene is highly overexpressed in human uterine serous carcinomas and carcinosarcomas and drives Matrix Metalloproteinase-2 ( MMP-2 ) in a subset of tumors

Abstract: Objectives Although uterine cancer is the fourth most common cause for cancer death in women worldwide, the molecular underpinnings of tumor progression remain poorly understood. The High Mobility Group A1 (HMGA1) gene is overexpressed in aggressive cancers and high levels portend adverse outcomes in diverse tumors. We previously reported that Hmga1 transgenic mice develop uterine tumors with complete penetrance. Because HMGA1 drives tumor progression by inducing matrix metalloproteinase (MMP) and other genes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 37 publications
1
19
0
Order By: Relevance
“…Even through a recent study showed miR-221 could suppress the expression of MMP2 74 , our reporter assay showed that neither miR-221-3p nor miR-222-3p had an effect on the 3′UTR of MMP2. Otherwise, recent studies indicated that HMGA1 could promote the migration and invasion in lung cancer and uterine carcinomas by directly targeted MMP2 as well as in pancreatic adenocarcinoma and gliomas through regulating MMP9 17 , 75 77 . Similarly, our results revealed that HMGA1 regulated the expression of MMP2 and MMP9.…”
Section: Discussionmentioning
confidence: 99%
“…Even through a recent study showed miR-221 could suppress the expression of MMP2 74 , our reporter assay showed that neither miR-221-3p nor miR-222-3p had an effect on the 3′UTR of MMP2. Otherwise, recent studies indicated that HMGA1 could promote the migration and invasion in lung cancer and uterine carcinomas by directly targeted MMP2 as well as in pancreatic adenocarcinoma and gliomas through regulating MMP9 17 , 75 77 . Similarly, our results revealed that HMGA1 regulated the expression of MMP2 and MMP9.…”
Section: Discussionmentioning
confidence: 99%
“…HMGA1 helps promote protumourigenic phenomena like proliferation, migration, and invasion in multiple ways: it activates the Akt/MMP9 cascade in pancreatic adenocarcinoma, HMGA1/MMP2 pathway in uterine carcinosarcomas, and blocks the expression of metastasis suppressor protein 1 in T‐cell leukaemia . Further, HMGA1 expression has been found to be induced by transforming growth factor beta (TGF‐β) signalling through specificity protein 1 and phosphatidyl inositol‐3 kinase, resulting in enhanced tumourigenic properties in breast carcinoma .…”
Section: Discussionmentioning
confidence: 99%
“…Breast cancer represents the most common cancer and is one of the leading causes of cancer mortality in women. Although the survival of breast cancer patients has improved due to advancements in diagnosis and treatment, the prognosis in many patients with breast cancer remains poor (Hillion et al, 2016). It has been reported that genetic markers including estrogen receptor (ER) (Deroo et al, 2006), BRCA (Miecznikowski et al, 2010), and HER-2/neu receptor (Hynes et al, 1994) were significantly associated with breast cancer severity.…”
mentioning
confidence: 99%